Human papillomavirus infection cytological colposcopic and histopathological abnormalities alterations in different age groups - Alves, Rosane R.F.; Teixeira, Tarnara S.; Netto, Joaquim C.A. (Brazilian Journal of Sexually Transmitted Diseases, 2003)
[...]